2006
DOI: 10.1093/annonc/mdj965
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term survival results of a randomized trial comparing gemcitabine/cisplatin and methotrexate/vinblastine/doxorubicin/cisplatin in patients with locally advanced and metastatic bladder cancer

Abstract: Long-term overall and progression-free survival following treatment with GC or MVAC are similar. These results strengthen the role of GC as a standard of care in patients with locally advanced and metastatic transitional-cell carcinoma (TCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 14 publications
1
69
0
3
Order By: Relevance
“…These results were comparable with the results from studies using the same gemcitabine-cisplatin combination against advanced transitional cell carcinoma 8,15,16 . However, the overall response rate (47.6%) and CR (14.3) in the GC therapy in this study is lower than the results reported by Khaled HM,et al 17 .…”
Section: Discussionsupporting
confidence: 82%
“…These results were comparable with the results from studies using the same gemcitabine-cisplatin combination against advanced transitional cell carcinoma 8,15,16 . However, the overall response rate (47.6%) and CR (14.3) in the GC therapy in this study is lower than the results reported by Khaled HM,et al 17 .…”
Section: Discussionsupporting
confidence: 82%
“…200 The 5-year survival rates between GC and MVAC were also similar. 201 A phase 3 trial of high-dose-intensity MVAC with recombinant human granulocyte colony-stimulating factor (G-CSF) versus MVAC alone demonstrated that high-dose-intensity MVAC enabled delivery of higher doses of chemotherapy in a shorter time, but there was no difference in survival between the 2 groups. 202 Paclitaxel is a drug that stabilizes microtubules and promotes their assembly, which results in an Mphase cell-cycle arrest.…”
Section: Urinary Diversionmentioning
confidence: 99%
“…5 Consequently, costs for chemotherapy were extrapolated from a multinational costing study that assessed the costs of gemcitabine/cisplatin in nonsmall cell lung cancer. 26 Because the administration, dosage, and number of cycles of chemotherapy is similar for the treatment of advanced lung cancer and bladder cancer, [27][28][29] we assumed that the chemotherapyrelated complications and medical oncology workload between the 2 disease sites would be similar. The cost of dying from cancer or from other causes was extrapolated from an ongoing comprehensive casecosting study for prostate cancer (unpublished data).…”
Section: Costsmentioning
confidence: 99%